A study on happiness index among government employees: a case study in Kota Bharu / Nadi@Latif Bacho ... [et al.] - Bacho, Nadi@Latif; Che Omar, Azman; Kairan, Omar; Shaari, Rustam (2010)
The ultimate concern of human kind is enjoying their lives with full of happiness. Hence, in the pursuit of happiness, one's shouldn't ignore the important domains of life that influence and contribute to the level of happiness. As such happiness is very subjective and yet the level of happiness varies from person to person. This research is set to study on happiness index among government employees resided in Kota Bharu.The purpose of this study is to determine the domain of life associated to government employees which will influence and contribute to their happiness. This study also enables to know the relationship between job satisfaction, pay satisfaction and life satisfaction with happiness index. The research design employed is descriptive study. The study uses both secondary and primary data. Of the 400 questionnaires distributed, 109 completed and useable for a 27.3% response rate respondents working at Kota Bharu. In the sampling procedure, random sampling techniques were employed. In analyzing the data, frequency, percentage, cronbach alpha, KMO were computed using SPSS. The study reveals that there are several domains or factors which contribute to happiness such as job satisfaction, pay satisfaction and life satisfaction. The researcher identifies that life satisfaction and pay satisfaction are significant in influencing the happiness index. However, job satisfaction is not significant in influencing towards the contribution to the happiness index among the government employees. As this research focus only the three domain of life which are job satisfaction, pay satisfaction and life satisfaction, future research should add more important domain of lives, the likes of religion, health, leisure time, political and economic situation to name a few.